SYMBOLIC INTERACTION OF ARAB ETHNICITY AS A CULTURAL IDENTITY IN A MULTICULTURAL SOCIETY - Riesta Ayu Oktarina; Mukhamad Ainul Yaqin (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Abstract Identity also needs to be built to be able to make a character or identification. The more identities created, it can also become known in the community. Ethnic Arabs have an identity as an identifier as a symbol of Arab ethnicity. The method to be used in this study is qualitative, while the approach is phenomenology. The type of qualitative research based on the type of literature or data collection research library can be obtained through relevant sources, books, research journals or conceptuals that have a close relationship with ethnic Arabs there are 2 symbols, namely: Use the surname dadalam full name. Surnames and Gamis Wear, The values contained in religion include having a good impression, having a reputation, loyalty, social class, and social moral standards.